Therapeutic Potential of Hydroxysafflor Yellow A on Cardio-Cerebrovascular Diseases - Bai, Xue; Wang, Wen-Xiao; Fu, Rui-Jia; Yue, Shi-Jun; Gao, Huan; Chen, Yan-Yan; Tang, Yu-Ping (Frontiers in Pharmacology, 2020)
The incidences of cardio-cerebrovascular diseases (CCVDs) are increasing worldwide, causing more and more serious public health burden. The pursuit of new promising treatment options is thus becoming a pressing issue. Hydroxysafflor yellow A (HSYA) is one of the most representative active quinochalcone C-glycosides in the florets of Carthamus tinctorius L., a medical and edible dual-purpose plant. HSYA has attracted much interest for its pharmacological actions in treating and/or managing CCVDs such as myocardial and cerebral ischemia, hypertension, atherosclerosis, vascular dementia, and traumatic brain injury, in the massive preclinical studies. In this review, we briefly summarized the mode and mechanism of action of HSYA on CCVDs based on these preclinical studies. And the therapeutic effects of HSYA against CCVDs were presumed to reside mostly in its antioxidant, anti-inflammatory and neuroprotective roles by acting on complex signaling pathways.